Training on Creating High-Value Patchwork Fabric Craft Products for PKK Women as an Application of Realistic Mathematics Education - Afnaria; Syahputra, MR.; Br. Sembiring, Metrilitna; Rambe, Isnaini Halimah; Oktariani, Dhia (Talenta Publisher, 2024)
This activity is implemented to apply the theories of plane geometry in making patchwork fabric crafts of high values and at the same time provide training for the members of PKK in Bingkat Village, Pegajahan District, Serdang Bedagai Regency. In serving the purpose, Realistic Mathematics Education may be adopted as an approach to be used to help participants comprehend the notion mathematics using real-world circumstances. In this case, the square theory is applied, giving the precise cloth cutting and sewing processes for good outputs that look nice. The seminar was scheduled to take one day, namely August 20, 2024, with the members of PKK who are in desperate need of a new business alternative because sales at Pasar Bengkel are falling. The training methods consisted of teaching the Trainees the skills to produce three-dimensional flowers from patchwork fabric and how to create Social Media Marketing of the products. Results from this training showed an increase in the N-Gain of participants' product creation skills at 0.75 and for the digital marketing, it was 0.74. Such an activity has resulted in three-dimensional beautiful flowers items and a better understanding of marketing methods among the participants. It was such an initiative that provided concrete solutions to the challenges of the partners and thus could make a very significant contribution toward local economic development. More training and mentoring are being envisioned to make sure that participants will be able to apply independently the knowledge and skills they have learned.